IMPROVING STUDENTS’ READING COMPREHENSION THROUGH STORY GRAMMAR STRATEGY AT SMP NEGERI 08 SATAP DODA BUNTA - Abdul Rabbi Arrasul; Yorib Lang (BABASAL English Education Journal, 2022)
The objective this research is to improve students’ reading comprehension through story grammar strategy at SMP Negeri 08 Satap Doda Bunta. This research used a pre-experimental research design with one group pretest and posttest design. The population of this research was the students of VIII grade of SMP Negeri 8 Satap Doda Bunta consisted of twenty-eight students. The sample of this research was all the population of the research. In collecting data, the researcher used test. The test consisted of pretest and posttest. Data were analyzed statistically. After being analyzed, it was found that the result of the t-counted was 9,245. With 27 degree of freedom, and a the significance level of 0,05, the t-table was 1,703.Therefore, the result of t-counted is greater than t-table. It is clear that the research hypothesis is accepted. In other words, story grammar strategy can effectively improve the reading comprehension of VIII grade students at SMP Negeri 8 Satap Doda Bunta.